First report on the antibacterial and anti-Fusarium activity of methanolic extract of the red alga Asparagopsis armata - L. Maidi; H. Gouzi; R. Hammoudi (Regulatory Mechanisms in Biosystems, 2025)
This research records the antibacterial and anti- F usarium activit y of the methanolic extract (MeOH) from the marine alga, Asparagopsis armata , collected in Algeria . The antibacterial activity was screened using the w ell diffusion method against five pathogenic bacteria strains: Escherichia coli , Pseudomonas aeruginosa , Bacillus cereus , Klebsiella pneumo nia e and Staphylococcus aureus . The anti- F usarium activity was evaluated using the direct contact method against four Fusarium species ( F . culmorum , F . graminearum , F . poae and F . avenaceum ). The results reve a led that the methanolic extract of A. armata demonstrated notable antibacterial activity against the tested strain s with an inhibition zone ranging between 10 . 2 and 40 .6 mm. The crude methanolic extract of A. armata exhibited significant antibacterial activity against S. aureus , K. pneumoniae and B. cereus with minimal inhibitory concentration ≤ 2 mg/m L , P. aeruginosa appears to be the most resistant strain to the methanolic extract, the MIC > 4.0 mg/m L . C oncentration of 80 mg/m L exhibit ed a total inhibition for all fungal strains except for Fusarium poae. The important activity of the extract was attributed to the volatile compounds such as phenol derivatives, halogenated and terpenoid compounds. The red marine alga Asparagopsis armata represent s an important source of new antibacterial and antifungal agents that can replace the chemical agents used for treatment of human infections and plant diseases.